Ambidexterity in Technology Sourcing: The Moderating Role of Absorptive Capacity - Rothaermel, Frank T.; Alexandre, Maria Tereza (Organization Science, 2009)
A firm's organizational and technological boundaries are two important demarcation lines when sourcing for technology. Based on this theoretical lens, four possible combinations of exploration and exploitation emerge. Applying an ambidexterity perspective to a firm's technology sourcing strategy, we hypothesize that a curvilinear relationship exists between a firm's technology sourcing mix and its performance. We further introduce a contingency element by proposing that a firm's absorptive capacity exerts a positive moderating effect on this relationship. We empirically test these hypotheses on a random, multi-industry sample of U.S. manufacturing companies. We find support for the notion that the relationship between technology sourcing mix and firm performance is an inverted U-shape. Moreover, higher levels of absorptive capacity allow a firm to more fully capture the benefits resulting from ambidexterity in technology sourcing.